Contraceptive and molecular function of a novel recombinant vaccine based human leukemia inhibitory factor on Balb/c mice: An experimental in vivo study. (November 2020) - Zare, Fateme; Amiri, Mohammad Mehdi; Hadinedoushan, Hossein; Dehghan-Manshadi, Mahdi; Mansouri, Fatemeh; Fesahat, Farzaneh; Saboor-Yaraghi, Ali Akbar
Highlights: rhLIF prevented pregnancy in a high percentage of female mice. The immunization of female Balb/c mice with rhLIF inhibited fertility. This protein can be as a suitable candidate for the human contraceptive vaccine. Abstract: The functional competence of leukemia inhibitory factor (LIF), as immunocontraceptive vaccine in mice, was investigated. Balb/c mice were divided into two groups of vaccinated and controls. The recombinant human LIF (rhLIF) protein and phosphate buffer saline was emulsified with Freund's adjuvant and injected into vaccinated and control groups, respectively. Theinhibition of implantation was evaluated in mice uterine. The concentration of secreted interferon-γ (IFN-γ) and interleukin (IL)-4 were measured in cultured splenocyte of mice stimulated by rhLIF. The expressions of immune responsive gene 1 (IRG-1), cochlin (COCH), amphiregulin (Ar), and heparin-binding EGF-like growth factor (HB-EGF ) genes were determined. Mice were assessed for inhibition of fertility after delivery, reversibility of immune response against rhLIF, and survival rate. Active immunization of mice with rhLIF resulted in reduction of the implantation and fertility rate up to 80.49% and 75%, respectively. All mice produced a high titer of anti-rhLIF antibodies in serums and vaginal fluids washes after 16 weeks; however, these antibodies were cleared from vaginal fluid washes after six months. A significant down-regulation in mRNA levels of IRG-1, Ar and HB-EGF was observed in vaccinated group compared to controls; however, no significant change in the expression profile of cochlin gene was detected. The results showed that rhLIF prevented pregnancy in a high percentage of female mice. Although the immunization of female Balb/c mice with rhLIF inhibited fertility and expression of genes associated with this molecule, further studies are needed to support this protein as a suitable candidate for contraceptive vaccine in mammals.